PERTAHANAN NILAI RELIGIUS MASYARAKAT MODERN DALAM NOVEL IMPIAN AMERIKA KARYA KUNTOWIJOYO - Rahaya, Ivana Septia; Subiyantoro, Slamet; Setiawan, Budhi (Universitas Andalas, 2020)
The change will always be experienced by the community, especially if it is already related to globalization. In addition to cultural degradation, the negative impact of globalization is lifestyle changes that are not following the values and norms of Indonesian society. At that time, religious values play an important role as a stronghold of negative things. The purpose of this study is to describe religious values by modern society amid globalization in the novel Impian Amerika by Kuntowijoyo. The data of this study are sentences or paragraphs describing the defense of religious values by modern society. The data source of this research is the Impian Amerika novel by Kuntowijoyo. The method used is descriptive qualitative with the technique of collecting recorded data and study of literature. Data analysis techniques using content analysis techniques. This research is important to do because, with the knowledge of religious values, a person will avoid negative things. Â Religious values will protect us from negativity.Â